17 Improving the workplace experience for pediatricians in an academic practice. (25th November 2019) - McLean, Heather; Lawson, Jennifer; Spears, Tracy; Milazzo, Angelo; Kline, Susan; McGann, Kathleen; Cunningham, Coleen; Reed, Ann
Abstract : Background: Physician burnout has a negative effect on the quality of care; however, effective interventions are lacking. Objectives: To identify and impact key drivers of physician workplace satisfaction in an academic pediatric department. Methods: A quality improvement approach was used to impact key drivers of faculty workplace satisfaction. In 2017, 2018, and 2019 faculty completed anonymous surveys that combined the Maslach Burnout Inventory(MBI) and Areas of Worklife Survey(AWS). Interventions included changes to compensation plan, clinical practice, departmental communication, workplace community, individual wellness, and culture. Descriptive statistics and data visualization were performed. Two-sided t-tests and ANOVA regression analysis were used to compare responses. Results: Survey completion rates were: 160/195 (82%) in 2019; 139/180 (77%) in 2018; and 155/171 (91%) in 2017; 101 physicians completed all three surveys. Statistically significant improvements were observed in reward (3.4 vs 3.3; p<0.05) and values (3.6 vs 3.5; p<0.05) domains of the AWS in 2019 and 2018 versus 2017. MBI average scores were similar in all three years, and remained significantly better than the general population in depersonalization (1.0 vs. 1.7; p<0.0001) and personal accomplishment domains (5.0 vs. 4.3; p<0.0001). There was no difference in the emotional exhaustion domain. Worse emotional exhaustion scores were reported in women (2.8 vs 2.1; p<0.05) and those working >75% clinical effort (2.8 vs 2.1; p<0.05). Conclusions: Interventions targeting the workplace improved physicians' experience of reward and values. Risk factors associated with a high emotional exhaustion score included female gender or individuals working >75% clinical effort.